Xenogeneic bone matrix immune risk assessment using GGTA1 knockout mice. (12th November 2018) - Shao, Anliang; Ling, You; Xu, Liming; Liu, Susu; Fan, Changfa; Wang, Zhijie; Xu, Bin; Wang, Chengbin
Abstract: Homeotransplantation of bones for replacement therapy have been demonstrated reliably in clinical data. However, human donor bones applicable for homeotransplantation are in short supply, which facilitates the search for suitable alternatives, such as xenografts grafts. The α-Gal antigen-related immune risk of xenografts directly affects the safety and effectiveness of the biomaterials and limits their applications in the clinic. The immune risk can be prevented by depletion or breaking anti-Gal antibody prior to transplant. Therefore, how to assess the immune risk of the bone substitutes and select the reliable animal research model become extremely important. In this study, we prepared lyophilized bone substitutes (T1) and Guanghao Biotech bone substitutes (T2, animal-derived biomaterials with α-Gal antigen decreased), aimed to assess the immune risk of xenografts bone substitutes on GGTA1 knockout mice. The α-Gal antigen contents of T1 and T2 were firstly detected by ELISA method in vitro . The bone substitutes were then implanted subcutaneously into GGTA1 knockout mice for 2, 4 and 12 weeks, respectively. The total serum antibody levels, anti-α-Gal antibody levels, inflammatory cytokine and splenic lymphocyte surface molecules were detected and histology analysis of skin and thymus were performed to systematically evaluate the immune response caused by the T1 and T2 bone substitutes in mice. In vitro results showed that the amount of α-Gal epitopes in T1 bone substitutes was significantly higher than T2 bone substitutes, and the clearance rate of α-Gal antigen in T2 bone substitutes achieved about 55.6%. Results of antibody level in vivo showed that the T1 bone substitutes group possessed significantly higher total IgG, IgM, IgA and anti-α-Gal IgG levels than T2 and control group, while T2 group showed no significant changes of these indexes compared with control. In terms of inflammatory cytokines, T1 bone substitutes showed evidently higher levels of IL-4, IL-12P70 and IL-10 than T2 and control, while T2 group was comparable to control. No changes in the levels of splenic lymphocyte surface molecules were found in the three groups (T1, T2 and control group) during the experimental periods. The pathological results demonstrated that the inflammatory response in T2 group was lighter than the T1 group, which was in accordance with the inflammatory cytokines levels. The above results indicated that the process of antigen removal effectively reduced the α-Gal antigens content in T2 bone substitutes, which caused little immune response in vivo and could be used as bone healing materials. This study also demonstrated that GGTA1 knockout mice can be used as a routine tool to assess the immune risk of animal-derived biomaterials.